Implementasi Pengembangan Karier, Kompetensi, dan Iklim Organisasi terhadap Efektivitas Kerja serta Dampaknya pada Kinerja Karyawan PT Putra Citnusa Pengelola Plaza Baru Ciledug Tangerang Banten - Novaliana, Novaliana; Airlanggia, Vita; Anton, Anton (Jurnal EMT KITA, 2026)
This study aims to analyze the Implementation of Career Development, Competence and Organizational Climate, on Work Effectiveness and Its Impact on Employee Performance at PT. Putra Citnusa, Manager of Plaza Baru Ciledug Tangerang Banten, This study uses a quantitative method with a descriptive and explanatory approach. Data were collected through a survey involving 128 employees of PT. Putra Citnusa, Manager of Plaza Baru Ciledug Tangerang Banten with a saturated sample method and processed using SEM PLS 3.0. The results of the study indicate that the variables of Career Development and Competence do not affect work effectiveness, while Organizational Climate has a positive and significant effect on work effectiveness, and the variable of work effectiveness affects employee performance.